Evaluation of Four Risk-Scoring Methods to Predict Long-Term Outcomes in Patients Undergoing Aorto-Bifemoral Bypass for Aorto-Iliac Occlusive Disease - García, Francisca; Marchena, Joaquín; Cabrera, Vicente; Hermida, María; Sotgiu, Enrico (International Journal of Angiology, 2012)
This study was done to determine the usefulness of the American Society of Anesthesiologists (ASA) classification, the comorbidity Charlson index unadjusted (CCIu),the comorbidity Charlson index adjusted by age (CCIa), and the Glasgow aneurysm score (GAS) for postoperative morbimortality and survival in patients treated with aorto-bifemoral bypass (AFB) for aorto-iliac occlusive disease (AIOD). A series of 278 patients who underwent AFB were restrospectively studied. For the CCIu, CCIa, ASA, and GAS, receiver operating characteristics curve analysis for prediction of morbidity showed area under the curves of 0.61 (p = 0.004), 0.59 (p = 0.026), 0.569 (p = 0.087), and 0.63 (p = 0.001), respectively. Additionally, univariate analysis showed that CCIa (p = 0.016) and GAS (p = 0.006) were associated significantly with an increased risk of developing complications. Furthermore, CCIa (p < 0.001) and GAS (p = 0.001) showed a significant association with survival. Finally, the variable age was related to morbidity (p = 0.004), mortality (p = 0.038), and survival (p < 0.001). The comorbididity and the age should be taken in account in clinical treatment decisions for patients with AIOD. The CCIa and GAS may play a role as predictive factors for postoperative morbidity and survival after AFB.
Keywords: atherosclerosis; peripheral arterial disease; risk factors; risk-scoring methods